Building a Home - Apel, Maria (My University, 2022)
This supplemental paper provides insight into the process of using video production (planning, filming, editing) as an access point to a local community center, Be Able Community. I build on lessons that I’ve learned throughout my time at KSU, focusing on the anthropological perspectives I’ve gained and especially those that intersect with the other disciplines I’ve studied: psychology, trauma studies. I reflect not only on how these lessons have served me during my time at K-State, but also on how I plan to carry them forward into the next phase of life.